(i) a2b – ab2 + 3a – 3b
(ii) x3 – 3x2 + x – 3
Answer :
(i) a2b – ab2 + 3a – 3b
Take out common in all terms,
ab(a – b) + 3(a – b)
(a – b) (ab + 3)
(ii) x3 – 3x2 + x – 3
x3 – 3x2 + x – 3
Take out common in all terms,
x2 (x – 3) + 1(x – 3)
(x – 3) (x2 + 1)
More Solutions:
- If x + 1/x = 2, then x2 + 1/x2 is equal to
- If x2 + y2 = 9 and xy = 8, then x + y is equal to
- (102)2 – (98)2 is equal to
- 1032 – 972/200 is equal to
- The value of 2492 – 2482 is
- If a+b+c=0, then the value of a3+b3+c3 is
- Solve the Expansions
- Find the expansions of the following :
- Simplify: (x – 2) (x + 2) (x2 + 4) (x4 + 16)
- Evaluate 1002 × 998 by using a special product.
- Prove that a3 + 8b3 + 27c3 = 18 abc